Budaya Perlawanan di Ranah Seni Indonesia: Produksi-diri Masyarakat, Habitus, Komodifikasi - Imam Setyobudi (Habitus : Jurnal Pendidikan, Sosiologi, dan Antropologi, 2017)
ABSTRACTThe realm of art just as a society is so full of conflict seized control of the course of history. Debate arises from the habitus of the dualism dichotomy. However, the current context with commodification influences the original dualistic shift of habitus to polysemic, polymorph, and polivocal. Commodification encourages the occurrence of cultural explosion so that live fragments of culture or sub-culture. This article utilizes the concept of community self-production, habitus, and commodification to answer the research question why is there an art resistance movement? The conspiracy of the interests of actors scattered in various agencies has undermined the aesthetic regime. keyword: the self-production of society, habitus, commodification ABSTRAKRanah seni seperti halnya suatu masyarakat begitu sarat konflik dalam rangka pegang kendali terhadap proses jalannya sejarah. Perdebatan muncul akibat adanya habitus dikotomi dualisme. Namun demikian, konteks terkini dengan hingar-bingar komodifikasi mempengaruhi pergeseran habitus yang semula dualistis menjadi polisemi, polimorf, dan polivokal. Komodifikasi justru membuka peluang terjadinya peledakan kebudayaan sehingga tinggal serpihan-serpihan budaya atau sub-budaya. Artikel ini memanfaatkan konsep produksi-diri masyarakat, habitus, dan komodifikasi untuk menjawab pertanyaan riset kenapa senantiasa muncul gerakan perlawanan seni? Persekongkolan kepentingan aktor-aktor yang tersebar dalam berbagai keagenan telah meruntuhkan rezim estetis.  Kata Kunci : masyarakat produksi, habitus dan komodifikasi